Analisis Peranan Sektor Pertanian dalam Perekonomian Wilayah di Kabupaten Simalungun Provinsi Sumatera Utara - SARAGIH, NOVAULINA; SURYAWARDANI, I GUSTI AYU OKA; SUDARMA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of the Role of the Agriculture Sector in the Regional Economy Simalungun Regency, North Sumatra The agricultural sector is the sector that provides the largest contribution to the economy of Simalungun Regency. The contribution of the agricultural sector to the economy of Simalungun Regency during 2016-2020 tends to increase over the last two years, while the growth rate of the agricultural sector has decreased. The purpose of this study is to determine the role of the agricultural sector in the regional economy in Simalungun Regency, whether it is a basic or non-basic sector. This research is a quantitative descriptive analysis. This research was conducted in Simalungun Regency, North Sumatra Province. This study uses secondary data in the form of GRDP data according to the business field of Simalungun Regency and North Sumatra Province in 2016-2020. The data was collected using the documentation method and analyzed using the  Location Quotient, Dynamic Location Quotient and Total Shift-Share  methods. The results showed that the agricultural sector became the basic sector in the present and the non-basic sector in the future, the changes were caused by location factors. The agricultural subsector is the basic, namely the food crops subsector, the plantation crops subsector and the agricultural and hunting services subsector. However, the food crops sub-sector and the plantation crops sub-sector will experience changes in their roles in the future due to economic structure factors.